PROBLEMATIKA GURU DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK KELAS VI DI SDS TARBIYATUL ISLAM SAMBAS - Hening Nurul Arestu (JURNAL ILMIAH EDUKATIF, 2022)
Learning contains changes in the desired behavior of students after taking a learning experience or teaching and learning process. But in reality, the education that has been implemented in schools is still not able to achieve this goal. This is due to the implementation of learning that is not optimal. For this reason, the government organizes the National Education system to increase faith and piety as well as noble morals in educating the life of the Indonesian nation. The purpose of this study is to reveal about: 1) Describe the problems of teachers in improving the learning discipline of grade VI students; 2) Describe and analyze the steps of the teacher in improving the learning discipline of class VI students; 3) Describe and analyze the supporting and inhibiting factors of the teacher in improving the learning discipline of class VI students, This study uses a qualitative approach and descriptive analytical research type. Data collection techniques using interviews, observation, and documentation study. The data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions and verification. Describing the problems of teachers in improving the learning discipline of grade VI students at Sds Tarbiyatul Islam Sambas, Sambas sub-district, Sambas district, the 2020/2021 school year are: a) differences in the awareness of students in applying discipline; b) the teacher has a goal of increasing discipline; c) instilling disciplined behavior according to the rules; and d) improve learning discipline by providing real examples of discipline application. Describing and analyzing the steps of the teacher in improving the learning discipline of class VI students at Sds Tarbiyatul Islam Sambas, Sambas sub-district, Sambas district, academic year 2020/2021, namely a) conveying school rules to students; b) make classroom rules relevant to school rules; c) prepare sanctions for students in the form of warnings, warnings and punishments; d) provide a form of sanctions that are applied in class, Describe and analyze the supporting and inhibiting factors of teachers in improving the learning discipline of grade VI students at Sds Tarbiyatul Islam Sambas, Sambas sub-district, Sambas district, academic year 2020/2021, namely a) Students' awareness to develop in class; b) achieve the progress of students in class; c) good cooperation between students in the classroom and cooperation between teachers and school principals and other teachers.